2014
DOI: 10.1194/jlr.m049726
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-apheresis reduces circulating microparticles in individuals with familial hypercholesterolemia

Abstract: Lipoprotein-apheresis (apheresis) removes LDL-cholesterol in patients with severe dyslipidemia. However, reduction is transient, indicating that the long-term cardiovascular benefits of apheresis may not solely be due to LDL removal. Microparticles (MPs) are submicron vesicles released from the plasma membrane of cells. MPs, particularly platelet-derived MPs, are increasingly being linked to the pathogenesis of many diseases. We aimed to characterize the effect of apheresis on MP size, concentration, cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…MVs generated during lipid apheresis may either circulate as single vesicles or adhere to blood cells, to each other, or to the adsorbent polymers, as supported by recent clinical data from patients treated with different LDL apheresis systems, which showed a reduction of circulating MVs during lipid apheresis . As to their interaction with blood cells, we found that leukocytes, in particular monocytes, are the primary targets for MV adhesion, confirming that monocytes are central actors for MV clearance and suggesting that blood cells are not only donors, but also recipients of MVs in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…MVs generated during lipid apheresis may either circulate as single vesicles or adhere to blood cells, to each other, or to the adsorbent polymers, as supported by recent clinical data from patients treated with different LDL apheresis systems, which showed a reduction of circulating MVs during lipid apheresis . As to their interaction with blood cells, we found that leukocytes, in particular monocytes, are the primary targets for MV adhesion, confirming that monocytes are central actors for MV clearance and suggesting that blood cells are not only donors, but also recipients of MVs in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In FH patients, plasma apheresis reduces circulating MV concentration, mainly platelet-derived MV AV + [88].…”
Section: Role Of Microvesicles In Dyslipidemiamentioning
confidence: 99%
“…Interestingly, the oxidative stress markers, such as plasma glutathione peroxidase and urinary 8-iso-prostaglandin F2 alpha, independently impacted on levels of platelet-derived vesicles [89] . Interestingly, the leptin can modulate platelet aggregation, shape platelet vesiculation and thereby links abdominal obesity and coagulopathy [90,91] . Moreover, leptin resistance rather than insulin resistance was found as a trigger for platelet activation that corresponds to increased risk of CV disease and CV events in patients with abdominal obesity, but not with diabetes mellitus [92,93] .…”
Section: Platelet-derived Vesicles In Dyslipidemia and Hypercholestermentioning
confidence: 99%